Strategi Publikasi Karya Ilmiah Pada Jurnal Internasional Dalam Bidang Hukum Keluarga Islam - Muslih, Muslih; Rahman, Rahman; Haqq, Muhammad Valiyyul (Maqasid: Jurnal Studi Hukum Islam, 2025)
Scientific publication is a crucial stage in scholarly development, particularly in the field of Islamic family law. This article aims to analyze strategies for publishing scientific works in the context of Islamic family law research in international journals. The methodology used is descriptive qualitative through literature study with content analysis of scientific publication guidelines and policy documents from various international publishers. Research findings indicate that successful international publication in Islamic family law requires a systematic approach encompassing innovative topic selection, structured methodology implementation, utilization of interdisciplinary perspectives, and understanding the editorial process of target journals. Key challenges include language barriers, differences in academic traditions, and limited access to global research networks. Recommended strategies include international collaboration, research capacity development, and integration of Islamic values with contemporary approaches. This research contributes as a practical guide for Islamic family law academics in enhancing the visibility of their scientific work on a global scale. Keywords: international publication, scientific work, Islamic family law, research methodology, reputable journals